Comprehensive Rehabilitation of the Punta del Este Shopping Center After Fire Damage - Álvaro Leez; María Noel Pereyra; Patricia Vila (Buildings)
On 6 August 2022, a fire devastated 80% of the Punta del Este Shopping Center in Maldonado, Uruguay. Originating in the kitchen of a supermarket, the fire ravaged the shopping center for 72 h before being brought under control. This article outlines the studies conducted to assess the fire’s impact on the building’s structure, as well as the strategies and rehabilitation project aimed at ensuring its stability and performance. An in-depth analysis of the concrete, reinforcements, and foundations was carried out using destructive and non-destructive testing. In total, over 150 concrete samples were collected for analysis, and the foundations were studied using indirect methods. Based on these analyses, actions were planned for each area, including structural repairs, reinforcements, or demolition. Due to the tight deadline for resuming commercial activity, special innovative structural solutions were designed to rehabilitate large severely damaged areas with the specific feature of avoiding demolition. This involved altering the static scheme of the structure, incorporating reinforcements and using slabs of the damaged structure as formworks. Complete demolition and subsequent reconstruction would have required timelines incompatible with the clients’ expectations, while the adopted solutions enabled the project to meet its objectives.